EVALUATION OF MULTICULTURAL EDUCATION - Mira Andriyani; Zulfahji Zulfahji (JURNAL TARBIYAH, 2025)
The phenomenon of cultural, ethnic, language, and religious diversity is an undeniable reality in both global and national contexts, including in Indonesia. Education, as a primary pillar of national development, plays a crucial role in responding to and managing this diversity constructively. Multicultural education presents an approach that recognizes, appreciates, and empowers diversity in all dimensions of education. Although the concept of multicultural education has long been of concern, evaluating, its implementation remains a significant challenge. This research aims to explore and analyze in depth the effectiveness of implementing multicultural education in the context of [Specify Specific Context, for example: elementary schools, madrasah aliyah, higher education, or other types of institutions. Through a comprehensive evaluation, it is hoped that the strengths, weaknesses, opportunities, and challenges faced in realizing inclusive and equitable education for all students can be identified